HUBUNGAN ANTARA KELENTUKAN OTOT TUNGKAI DENGAN KETEPATAN SERVIS ATAS MENGGUNAKAN KAKI BAGIAN DALAM PADA ATLET CLUB SEPAKTAKRAW GEMILANG JAYA PEKANBARU - Andika Pradana Efendi; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The Problem in this research is a upper service accuracy of athlete at Gemilang Jaya Sepaktakraw Club Pekanbaru were still lack of improvement, so that they often stuck on the net and ball go out of the field, caused of the service missed by the players is the lack of flexibility leg muscles of the ball floating in the air. In this research aims to find out wether there is the any correlation between flexibility leg muscles and on upper service accuracy by using inner leg at Gemilang Jaya Sepaktakraw Club Pekanbaru. The type of this research is Correlation Product Moment which has aims to find out level of the correlation between the independent variable (X) and the dependent variable (Y). The Technique of sampling is representative athletes at Gemilang Jaya Sepaktakraw Club Pekanbaru who can truly represent, which consisted of 6 athletes. This research was conducted at field of Gemilang Jaya Sepaktakraw Club Pekanbaru. Research instrument used that test of leg mucles flexibility with split test and upper service accuracy with service skill test. Based on the data analysis and discussion before showed that was proven with TCount is 0.321 and Ttable is 0.319. It means Tcount > Ttabel in the level ɑ= 0.05. It can be concluded that there is the any correlation between flexibility leg muscles on upper service accuracy by using inner leg at Gemilang Jaya Sepaktakraw Club Pekanbaru. In other words, the alternative hypothesis of this research was accepted.Keywords: Flexibility Leg Muscles, Upper Service Accuracy.